Pendidikan Kesehatan Tentang Masalah Persalinan Kala I - Regina Pricilia Yunika; Yadul Ulya; Siskha Maya Herlina (LP4M STIKes Karsa Husada Garut, 2024)
Introduction: Childbirth is a physiological process, starting from the opening of the cervix to the birth of the baby and placenta. Many factors influence childbirth, both from maternal and fetal factors and also from factors that help and accompany childbirth. In the first stage of labor, the active phase carries risks such as weak or irregular contractions, slow opening of the cervix, bleeding, pain and loss of amniotic fluid. This can cause high maternal mortality rates (MMR). The aim is to increase pregnant women's knowledge about problems in the first stage of labor. Methods: Counseling, discussion, question and answer, as well as pretest and posttest. Results: There was an increase in pregnant women's knowledge about problems in the first stage of labor. The increase can be seen from the data on the number of pregnant women who have good knowledge, from 60.7% increasing to 85.7% after receiving health education, where the increase was 25%. Meanwhile, the number of pregnant women who have sufficient and insufficient knowledge has decreased. The percentage decrease in knowledge of pregnant women in the sufficient category was 7.1% and there were no pregnant women who had insufficient knowledge. Conclusion: There is an increase in knowledge between before being given health education and after being given health education.